Aerobic microbial oxidation of hydrocarbon gases: Implications for oil and gas exploration. (May 2019) - Li, Jing; Liu, Changling; He, Xingliang; Santosh, M.; Hu, Gaowei; Sun, Zhilei; Li, Yanlong; Meng, Qingguo; Ning, Fulong
Abstract: The molecular and carbon and hydrogen isotope compositions associated with the aerobic consumption of methane (Cl ), ethane (C2 ) and propane (C3 ) were determined from incubations of marine sediments collected from the seafloor surface of the gas- and oil-bearing Bohai Bay in eastern China. The fresh sediment samples were incubated aerobically at 28 °C and treated with three types of hydrocarbon gas mixtures as follows: mixture I (C1 :C2 :C3 = 100:0:0), II (C1 :C2 :C3 = 99.00:0.70:0.30) and III (C1 :C2 :C3 = 79.96:10.04:10.00), corresponding to incubations i, ii and iii, respectively. All the hydrocarbons are of thermogenic origin, except C1 (microbial) in incubation ii. The oxidation of C1 -C3 was observed in all three treatments, with variations in carbon isotope fractionation factors (εC ) of C1 and average values of −10.5 ± 0.1, −5.7 ± 1.6, and −10.9 ± 2.9, respectively. The hydrogen isotope fractionation factors (εH ) of C1 in the three incubations also display variation, with average values of −118.4 ± 3.0, −68.3 ± 15.0 and −56.3 ± 8.4, respectively. Experiments with thermogenic C1 display greater carbon fractionation than those with microbial C1 . The εC and εH values for C2 and C3 were obtained only in incubation iii. Compared to C1, C2 and C3 exhibit weaker carbon isotope fractionation but stronger hydrogen isotope fractionation. The fractionation factors presented in this study can be applied to estimate the extent of C1 -C3 oxidation in natural environments, especially at seafloor and terrestrial seeps where aerobic microbes are commonly present. Our study has important implications in oil and gas exploration, with an alert for exercising caution when using the molecular and isotopic characteristics of hydrocarbon gases to evaluate the gas sources because these are susceptible to aerobic microbial oxidation. Highlights: Experimental evaluation of aerobic oxidation of methane (Cl ), ethane (C2 ), propane (C3 ). C1 -C3 display different hydrogen and carbon isotope fractionation patterns. Aerobic microbial oxidation can erase genetic information of hydrocarbon gas.